Permittivity-asymmetric chiral metasurfaces empowered by bound states in the continuum - Li, Yang; Mao, Yu; Yin, Shenwei; Zhou, Yi; Sun, Zefa; Tang, Zhixiang (Frontiers in Physics, 2025)
The intrinsic chirality of natural materials is usually weak or absent. To enlarge circular dichroism, chiral metasurfaces supporting bound states in the continuum have been widely investigated. These chiral metasurfaces have demonstrated considerable potential to achieve high quality (Q) factors but require ultra-small structure asymmetry and complicated fabrication processes. Here we propose a novel approach to break the in-plane symmetry of the structure by introducing refractive index perturbations. Furthermore, we demonstrate the efficient intrinsic chiral emission from resonant metasurfaces which are composed of two slant titanium dioxide (TiO2) bars arranged on a square lattice. Numerical calculations indicate that the intrinsic chirality of our metasurfaces at normal incidence achieves near-unity circular dichroism of 0.99 and an ultra-high Q factor exceeding 106. The relationship between the two perturbations and CD and Q factor has also been studied, offering the flexibility to enhance and tailor chirality and Q factor simultaneously. Our chiral metasurfaces may lead to applications in chiral lasers, chiral light detectors, chiral biosensing, and chiral nonlinear filters.